Referenciação, argumentatividade e interação discursiva: uma experiência didática com o texto dissertativo-argumentativo no 9° ano - Silva, Márcio Leandro (2018)
This research discusses the process of reference as a procedural and discursive activity, directly related to argumentation and communicative intentionality, in argumentative- dissertative texts of 9th grade elementary school students from a Municipal School located in the city of Pocinhos-PB. The justification for its realization was due to the students difficulties regarding the writing of these texts. Thus, based on a systematized practice of writing and rewriting this type of text, Thus, based on a systematized practice of writing and rewriting of this text modality, the objective is to analyze how the student and producer of argumentative-dissertative text linguistically and discursively uses the marks of reference for the production of meanings, argumentative- discursive texts produced and textual progression. In this sense, the research develops from the contributions of textual linguistics and studies on textual genre. For this, the work is based on the theoretical fundamentals of authors that support the sociodiscursiva and interactional perspective of the language, such as Antunes (2003, 2005); Marcuschi (2005, 2008); Plato & Fiori (1990, 2006) and authors who support the theoretical perspective of textual genres, such as Bakhtin (1979,1981,1992,1997, 2010); Bronckart (1999); Marcuschi (2008). Specifically, with regard to the study on referential expressions and argumentation, we take as reference the studies of Cavalcante (2003,2009); Koch (1984, 1989, 2002, 2005) and Magellan (2013). In order to base our discussion about the dissertation genre, we are guided by the theoretical apparatuses of Souza (2003) and Xavier (2010). In order to orient our discussion about the practice of textual production in the Portuguese language classes of elementary school we used the guidelines of the National Curriculum Parameters of Portuguese (BRASIL, 1998) and the work of writing and textual rewriting was developed according to the methodological orientation of the script of a didactic sequence defended by Dolz, Noverraz & Schneuwly (2004), considering, as hypotheses, that: 1) a systematized teaching of writing from the didactic sequence allows the improvement of the production of argumentative texts of the order of the dissertation, overcoming the plastered limits of this genre and positioning it beyond the walls of the school; 2) this teaching facilitates the proper use of the elements of reference and, consequently, the development of consistent argumentation revealing how students understand the world in which they live and how they defend their theses in it. Thus, this work presents as contribution to the improvement of the dissertation production process by the students, regarding the use of reference mechanisms that trigger the construction of argumentativity.